MODERN ALGORITHMS TO IDENTIFY PLAGIARISM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Nowadays information technology industry is growing extremely fast. To solve business needs, address researcher demand for problem solving a lot of programs are built from scratch. However, not all developers are fair enough to align their products with the corresponding library or another (open source) product licenses, i.e. copyrights are being violated, intentionally or due to familiarization with another source code. To address this issue in past decade multiple plagiarism detection techniques and algorithms were invented. Despite the fact, that many of them are capable of code comparison on meta-level, modern Integrated Development Environments (IDEs) provide convenient way to modify program source code without actual re-writing, preserving the original code workflow and avoiding plagiarism detection. This paper will compare and identify available approaches to apprehend this issue, as well as provide insights for the future this problem mitigation.